Analisis Kebutuhan Bahasa Inggris Mahasiswa Jurusan Ekonomi Syariah: Studi Kasus Mahasiswa Ekonomi Syariah Institut Agama Islam Negeri Metro - Ninsiana, Widhiya; Nawa, Agus Trioni (Tapis: Jurnal Penelitian Ilmiah, 2019)
This developmental research was conducted to compose the learning material specifically for Islamic Economics students of Economics and Islamic Business Faculty. Basically, there are differences between Conventional Economics and Islamic Economics. Their striking differences lie in several terms used for mentioning practices in their implementations. The method used adopted from the steps of product development developed by Sugiono[1]. Before composing the development design, researchers conducted 2 aspects of analysis, namely target needs and learning needs which were developed into questionnaires to investigate listening, speaking, reading, writing, grammar, and vocabulary. The data analysis resulted that there were no significant differences needed among six linguistic components above. However, it needed accentuation directly on all four linguistic skills (listening, speaking, reading, writing). Besides, the learning technique used during the English learning process is Cooperative Learning. [1] Sugiyono, Metode Penelitian Pendidikan (Bandung: Alfabeta, 2015), h. 409.